PERAN KOMIK DIGITAL DALAM MENDUKUNG PEMBELAJARAN VISUAL DAN PENGUATAN KARAKTER PESERTA DIDIK SEKOLAH DASAR - Sugiantari, Ni Komang Sri; Winangun, I Made Ari; Wati, Ni Nyoman Kurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Advances in digital technology in elementary education encourage the use of creative, interactive learning media that align with students' needs. One widely developed medium is digital comics, which combine text, illustrations, color, and storylines in an easy-to-understand visual display. This study aims to examine the role of digital comics in supporting visual learning and strengthening the character of elementary school students. The method used was a literature review with a descriptive analytical approach. Data were obtained through a review of ten scientific articles from the 2022–2026 period selected based on inclusion criteria. These criteria included empirical research on the use of digital comics in elementary education, while articles that did not align with the focus of the study were eliminated. Data analysis techniques used were content analysis and thematic synthesis. Students' conceptual understanding, motivation, participation, literacy skills, and independent learning can be improved through the use of digital comics. In addition, digital comics also support character building by instilling the values ​​of honesty, responsibility, cooperation, discipline, and environmental awareness presented in contextual and engaging stories. The novelty of this study lies in the integrative synthesis that combines various findings regarding the role of digital comics in supporting the knowledge and attitudes of elementary school students.